Effect of Parenteral Fluoroquinolone Administration on Persistence of Vancomycin-Resistant Enterococcus faecium in the Mouse Gastrointestinal Tract - Donskey, Curtis J. (American Society for Microbiology, 2004)
We examined the effect of subcutaneous fluoroquinolone antibiotic administration on persistence and density of vancomycin-resistant Enterococcus faecium stool colonization in mice. Levofloxacin and ciprofloxacin did not promote colonization in comparison to saline controls, whereas moxifloxacin and gatifloxacin promoted persistent overgrowth in a dose-dependent fashion.